Angiolymphoid Hyperplasia with Eosinophilia on the Palm - Kim, Seong Min (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2010)
Angiolymphoid hyperplasia with eosinophilia (ALHE) is an uncommon dermal angioproliferating tumor, characterized by red to brown papules or nodules on the head and neck, though also occurring in the mouth, trunk, extremities and inguinal area. The palm is a very unusual site for ALHE, and there have been very few cases reported globally thus far. ALHE can be pruritic and painful and histopathologic findings show vascular proliferation with infiltration of eosinophils and lymphocytes in the dermis. Plump endothelial cells protrude into the lumen. We report a case of ALHE occurring at an unusual site, the right palm, in a 62-year-old man, who had suffered from a solitary pinkish-colored, central depressed round hyperkeratotic plaque on his palm for 4 years. On the basis of clinical and histopathologic data, a diagnosis of ALHE was made. To our knowledge, this is the first report of ALHE on the palm in Korean dermatologic literature.